The Impact of Implementing a Specific Time Work Agreement (PKWT) on the Performance of Contract Employees at PT Yachiyo Trimitra Indonesia - Fauzobihi, Fauzobihi; Lamet, Bonaventura; Syaifullah, M. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In Indonesia, matters related to how work is carried out always begin with an agreement between the employer and the recipient of the work through a written or verbal work agreement. An employment agreement is made to determine the boundaries between what are the rights and obligations of the employee and what are the rights and obligations of the employer (employer). Meanwhile, if in carrying out work that has been mutually agreed upon in a written agreement, one of the parties violates or behaves outside of what has been agreed upon and harms one of the parties or violates the provisions of the law, then the work agreement can be canceled and the rights and obligations of the parties must be resolved through a dispute resolution mechanism by referring to the applicable laws. Of course, the work agreement text that has been mutually agreed between the employer and the recipient of the work is also an important document for resolving disputes between the parties. Since the promulgation of Law Number 11 of 2020 concerning Job Creation, especially the regulations contained in Government Regulation Number 35 of 2021 concerning